2020
DOI: 10.1111/geb.13073
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting latitudinal patterns in diversity and stability in a high‐latitude species‐rich moth community

Abstract: Aim Biodiversity is currently undergoing rapid restructuring across the globe. However, the nature of biodiversity change is not well understood, as community‐level changes may hide differential responses in individual population trajectories. Here, we quantify spatio‐temporal community and stability dynamics using a long‐term high‐quality moth monitoring dataset. Location Finland, Northern Europe. Time period 1993–2012. Major taxa studied Nocturnal moths (Lepidoptera). Methods We quantified patterns of change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 94 publications
11
37
1
Order By: Relevance
“…2). These results mirror findings from another recent long-term study showing opposing abundance and diversity trends (45). Together, our results indicate that recent abundance increases are driven by a small number of dominant taxa.…”
Section: Of 8 | Pnassupporting
confidence: 90%
“…2). These results mirror findings from another recent long-term study showing opposing abundance and diversity trends (45). Together, our results indicate that recent abundance increases are driven by a small number of dominant taxa.…”
Section: Of 8 | Pnassupporting
confidence: 90%
“…Such patterns were, for example, observed in vascular plants at coarse scales in Europe due to the extinction of rare native species and spread of alien species 38 . Thus, temporal changes in taxonomic composition, i.e., turnover, are likely to be more sensitive than simply taxonomic richness (i.e., alpha-diversity) and abundance in responses to global change 39,40 . Accordingly, we show that temporal changes in taxon turnover are more pertinent across biogeoregions than the other three studied biodiversity metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Other multidecadal declines in moth faunas have been reported from Europe (e.g., refs. [21][22][23][24].…”
Section: Chronology Of Moth Declinesmentioning
confidence: 99%
“…Spatially, moth trends vary at continental, regional, and even local scales, which suggests that different stressors are in play. While patterns of moth decline are prevalent across western, central, and northern European countries (17,(21)(22)(23)(24)26), typically, there is considerable within-country heterogeneity. Conrad et al (17) found that total abundance of macrolepidopterans decreased significantly (by 44%) in the southern half of GB over the period 1968-2002, but showed no overall change in the northern half.…”
Section: Moth Biodiversity Changes Are Spatially and Taxonomically Hementioning
confidence: 99%